Auditory perception dominates in motor rhythm reproduction. (June 2022) - Hildebrandt, Alexandra; Grießbach, Eric; Cañal-Bruland, Rouwen
It is commonly agreed that vision is more sensitive to spatial information, while audition is more sensitive to temporal information. When both visual and auditory information are available simultaneously, the modality appropriateness hypothesis predicts that, depending on the task, the most appropriate (i.e., reliable) modality dominates perception. While previous research mainly focused on discrepant information from different sensory inputs to scrutinize the modality appropriateness hypothesis, the current study aimed at investigating the modality appropriateness hypothesis when multimodal information was provided in a nondiscrepant and simultaneous manner. To this end, participants performed a temporal rhythm reproduction task for which the auditory modality is known to be the most appropriate. The experiment comprised an auditory (i.e., beeps), a visual (i.e., flashing dots), and an audiovisual condition (i.e., beeps and dots simultaneously). Moreover, constant as well as variable interstimulus intervals were implemented. Results revealed higher accuracy and lower variability in the auditory condition for both interstimulus interval types when compared to the visual condition. More importantly, there were no differences between the auditory and the audiovisual condition across both interstimulus interval types. This indicates that the auditory modality dominated multimodal perception in the task, whereas the visual modality was disregarded and hence did not add to reproduction performance.